Characteristic and Introspection of Road Traffic Injuries in China from 2012 to 2017 - Huiting Yu; Chan Nie; Yanna Zhou; Xue Wang; Haiyan Wang; Xiuquan Shi (Tehran University of Medical Sciences, 2021)
Background: To analyze whether the area differences of RTIs (road traffic injuries, RTIs) caused by unequal development in China, provide suggestions for the prevention of the RTIs. Methods: The data of RTIs in China was collected from the authoritative official website and yearbook of China. Results: Total RTIs in the East was the highest (RTIs frequency: 591789; injured people: 600611; death toll: 168885; economic loss: 27.22 billion RMB), followed by the Center (RTIs frequency: 321807; injured people: 352769; death toll: 91966; economic loss: 23.90 billion RMB) and the lowest in the West (RTIs frequency: 289482; injured people: 332517; death toll: 101095; economic loss: 16.35 billion RMB). The multivariate linear correlation and regression showed that the characteristic of RTIs was highly related with GDP (r=0.99, P < 0.001). Conclusion: The economically developed areas had a large amount of traffic damages. The government should focus on preventing high RTIs in the East and high death tolls in the West.